Myths of Chinese New Year Traditions Viewed from Maslow's Hierarchy of Needs Theory: Indonesian - LINDAWATI, AMELIA; Listyo Yuwanto (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This study aims to explore how myths in the Chinese New Year celebration traditions reflect or represent the levels of needs in Abraham Maslow's hierarchy of needs theory. Indonesia, as a country with diverse ethnicities and cultures, has a Chinese ethnic community that celebrates Chinese New Year as an important tradition. This celebration not only functions as a cultural ritual but also fulfills basic human needs. Based on a literature review method, this study analyzes various myths and traditions of Chinese New Year and relates them to Maslow's hierarchy of needs, including physiological needs, safety, love and belonging, esteem, and self-actualization. The results show that the Chinese New Year tradition plays a significant role in fulfilling these needs. Rituals such as family dinners, house cleaning, and giving red envelopes not only meet basic needs but also create a sense of security, love, and esteem within the Chinese ethnic community. Furthermore, this study applies Hofstede's cultural dimensions to deepen the understanding of how the Chinese New Year tradition supports the structure and cultural values of the Chinese, as well as its contribution to psychological and social well-being. This research provides valuable insights for cultural anthropology and social psychology studies and enriches appreciation for the existing cultural heritage.Keywords: Myth, Chinese New Year, Chinese, Psychology, Maslow